2011
DOI: 10.1161/circresaha.110.232306
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Stress Mediates Angiotensin II–Induced Cardiac Hypertrophy and Gαq Overexpression–Induced Heart Failure

Abstract: Rationale Mitochondrial dysfunction has been implicated in several cardiovascular diseases; however, the roles of mitochondrial oxidative stress and DNA damage in hypertensive cardiomyopathy are not well understood. Objective We evaluated the contribution of mitochondrial reactive oxygen species (ROS) to cardiac hypertrophy and failure by using genetic mouse models overexpressing catalase targeted to mitochondria and to peroxisomes. Methods and Results Angiotensin II increases mitochondrial ROS in cardiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
411
5
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 467 publications
(436 citation statements)
references
References 33 publications
(38 reference statements)
17
411
5
3
Order By: Relevance
“…There are many reasons why a human heart can fail, but the available evidence suggests that a functional decline of mitochondria is one of the major mechanisms underlying heart failure progression [2][3][4] . Impaired mitochondria provoke energy-generation defects, the increased production of harmful reactive oxygen species (ROS), and a greater propensity to trigger apoptosis 5 .…”
mentioning
confidence: 99%
“…There are many reasons why a human heart can fail, but the available evidence suggests that a functional decline of mitochondria is one of the major mechanisms underlying heart failure progression [2][3][4] . Impaired mitochondria provoke energy-generation defects, the increased production of harmful reactive oxygen species (ROS), and a greater propensity to trigger apoptosis 5 .…”
mentioning
confidence: 99%
“…(120) Mechanisms may include mitochondrial biogenesis that does not keep up with the increasing demand (121), mitochondrial uncoupling and decreased substrate availability, (122) and increased mitochondrial DNA deletions. (123) Studies have demonstrated that telomere dysfunctionactivated p53 directly leads to mitochondrial and metabolic compromise through the repression of the master regulators of mitochondrial biogenesis and function, peroxisome proliferator-activated receptor gamma coactivator (PGC)-1a and PGC-1b. (53) PGC repression is associated with a profound compromise in mitochondrial biogenesis and function and subsequent decline in ATP generation, indicating that a fundamental problem of energy maintenance drives the aging process.…”
Section: Cardiovascular Agingmentioning
confidence: 99%
“…NADPH oxidase activated by Ang II is the primary source of ROS that produces mitochondrial dysfunction [140]. The effects are due to both NOX4 and NOX2, which are upregulated by Ang II in a mitochondrial ROS-independent and dependent manner, respectively [141].…”
Section: Heart and Oxidative Stressmentioning
confidence: 99%